Is Cleft Severity Correlated With Intrinsic Growth Pattern? Observation From Unoperated Adult Patients With Submucous Cleft Palate. Issue 6 (September 2017) - Cao, Congcong; Xu, Xue; Shi, Bing; Zheng, Qian; Li, Jingtao
Abstract : Objective: This study aimed to evaluate the craniofacial morphology of unoperated adult submucous cleft palate (SMCP) patients and to explore the possible correlation between the intrinsic growth insufficiency of the maxillofacial complex and the severity of the cleft. Materials and Methods: A total of 20 unoperated SMCP patients, 20 unoperated overt cleft palate (OCP) patients, and 32 normal controls, ages between 18 and 30, were included for cephalometric analysis. One-way ANOVA and rank-sum tests were used for comparison, and the threshold of significance was at 95% ( P  < 0.05). Results: Sagittal maxillary length (ANS-PMP, A-PMP, Ba-ANS) and mandibular ramus length (Ar-Go) were significantly smaller in the SMCP and the OCP groups than in the control (normal > SMCP = OCP). Maxillary protrusion (∠ S-N-ANS, ∠ S-N-ANS) was similar between the SMCP group and the control, but significantly reduced in the OCP group (normal = SMCP > OCP). Significant differences in ∠ A-N-B were found between each of the 3 groups (normal > SMCP > OCP). Conclusion: Compared with normal, unoperated adult SMCP patients were of smaller mandible and shorter maxillae, but almost normal maxillary protrusion. Overt clefts demonstrated significantly more evident maxillary retrusion and crossbite than SMCP, indicating a correlation between the cleft severity and the intrinsic growth pattern of the maxillofacial complex.